Preparation of Ni3Fe2@NC/CC Integrated Electrode and Its Application in Zinc-Air Battery - Hu, Hui; Ling, Xiaofei; Tan, Chaogui; Lin, Jianguo; Han, Xiaopeng; Hu, Wenbin (Frontiers in Chemistry, 2020)
Reasonable design and development of a low-cost and high-efficiency bifunctional electrocatalyst for oxygen evolution reaction (OER) and oxygen reduction reaction (ORR) is essential for promoting the development of Zinc-air battery technology. Herein, we obtained an integrated catalytic electrode, NiFe nanoparticles supported on nitrogen-doped carbon (NC) directly grown on the carbon cloth (designated as Ni3Fe2@NC/CC), by pyrolysis of bimetallic NiFe metal-organic framework (MOF) precursor. There is a synergistic effect between nickel and iron component, which enhances the bifunctional catalytic activity. In addition, the underlying carbon cloth is conducive to the efficient electron transfer and also benefits the uniform loading of catalytically active materials. Thus, the integrated electrode shows good OER/ORR dual-functional catalytic performance, and the OER overpotential is much lower than that of the traditional drop-coating electrode and precious metal catalyst (IrO2). Moreover, the Ni3Fe2@NC/CC integrated electrode used in zinc-air batteries shows good flexibility and cycle stability. Our findings provide a new avenue for the development of efficient and stable bifunctional oxygen electrocatalysts.